Development and validation of a survey on reproductive health behaviors to reduce exposure to endocrine-disrupting chemicals in Koreans - Hye Jin Kim; Sung Hae Kim; So Young Choi; Gisoo Shin (Frontiers in Reproductive Health)
IntroductionRecently, issues related to climate change and endocrine-disrupting chemicals have come to the forefront. In particular, the pursuit of convenience has led to increased exposure to endocrine-disrupting chemicals in daily life, posing threats to reproductive health, including infertility and cancer. Therefore, this study aims to develop a questionnaire to assess the reproductive health behaviors of Koreans for reducing exposure to endocrine-disrupting chemicals, and to verify its reliability and validity.Materials and methodThis methodological study involved 288 adult men and women in South Korea and conducted item analysis, exploratory factor analysis, and confirmatory factor analysis.ResultsThe developed survey questionnaire consists of four factors and 19 detailed items related to reproductive health behaviors and reproductive health promotion behaviors through the main exposure routes of endocrine-disrupting chemicals: food, respiratory pathways, and skin absorption.ConclusionBased on the results of this study, it is hoped that research on reproductive health behaviors aimed at reducing EDC exposure will expand, considering various environments such as national and ethnic differences.